2020
DOI: 10.1002/lno.11470
|View full text |Cite
|
Sign up to set email alerts
|

A multistressor model of carbon acquisition regulation for macroalgae in a changing climate

Abstract: It is widely hypothesized that noncalcifying macroalgae will be more productive and abundant in increasingly warm and acidified oceans. Macroalgae vary greatly in the magnitudes and interactions of responses of photosynthesis and growth to multiple stressors associated with climate change. A knowledge gap that exists between the qualitative "macroalgae will benefit" hypothesis and the variable outcomes observed is regulation of physiological mechanisms that cause variation in the magnitudes of change in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Increased pCO 2 levels and low-light intensities are two processes that can result in a down-regulation or loss of CCMs (Hepburn et al, 2011;Raven et al, 2011;Cornwall et al, 2012;Dudgeon and Kübler, 2020). Hepburn et al (2011) found that conspecific macroalgal species grown in low-light habitats had a higher reliance on CO 2 diffusion than those grown at high-light habitats suggesting that under high-light intensities CCMs are necessary for keeping up with demand for inorganic carbon for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased pCO 2 levels and low-light intensities are two processes that can result in a down-regulation or loss of CCMs (Hepburn et al, 2011;Raven et al, 2011;Cornwall et al, 2012;Dudgeon and Kübler, 2020). Hepburn et al (2011) found that conspecific macroalgal species grown in low-light habitats had a higher reliance on CO 2 diffusion than those grown at high-light habitats suggesting that under high-light intensities CCMs are necessary for keeping up with demand for inorganic carbon for photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the effect of warming is also generally greater than the effect of increasing pCO 2 on Ulva sp. (Dudgeon and Kübler, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of macroalgae is closely related to algal photosynthesis (Lobban et al, 1985;Xu and Gao, 2009). Light provides the initial energy for photosynthesis, and the increase in culture light level can usually promote the photosynthesis of macroalgae by affecting electron transfer, pigment synthesis, and/or the activity of enzymes associated with carbon utilization (Xu et al, 2014;Wu et al, 2018;Dudgeon and Kübler, 2020;Eismann et al, 2020). In this study, a higher culture light level induced a greater maximum net photosynthesis rate, which indicated a higher photosynthetic capacity, and ultimately contributed to the higher growth rate of S. muticum.…”
Section: Discussionmentioning
confidence: 99%
“…Calcareous macroalgae are negatively impacted while noncalcareous macroalgae are hypothesised to be either unaffected or benefit from anthropogenic climate change. However, the responses of non-calcareous macroalgae are highly variable within or between species, especially among generic co-varying traits such as rates of photosynthesis and growth Dudgeon & Kübler, 2020). Studies based on laboratory experiments and modelling (Dudgeon & Kübler, 2020) suggest that the responses of macroalgae to climate change stressors may be influenced by local habitat profile and may be species-specific (Ji & Gao, 2021).…”
Section: The Variability In Responses To Oa and Environmental Changementioning
confidence: 99%